The age of doubt - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2012)
One night, Inspector Montalbano dreams of a stormy sea, which he knows represents unease and loss of control. The next day, a boat is found in the port of Vigata, and within it, the body of a disfigured corpse. The waterfront has also drawn in an eighty-five-foot luxury boat passengered by fifty carefree souls and a somewhat shadowy crew. They will have to stay in Vigata until the investigation is over--the man, it seems, was poisoned. However, right now, it is the yacht's owner and sailors Montalbano is focused on.